2014
DOI: 10.1177/1550059413515656
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brain Functional Changes in High-Frequency Repetitive Transcranial Magnetic Stimulation in Treatment-Resistant Depression

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a treatment procedure that uses magnetic fields to stimulate nerve cells in the brain, and is associated with significant improvements in clinical symptoms of major depressive disorder (MDD). The effect of rTMS treatment on the brain can be evaluated by cordance, a quantitative electroencephalography (QEEG) method that extracts information from absolute and relative power of EEG spectra. In this study, to analyze brain functional changes, pre- and post-rTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cordance, which is related to absolute and relative spectral powers derived from the resting EEG, increased after HFL-rTMS in both delta and theta bands at left frontal and all right electrodes, except for the F8 electrode, in responders, whereas it decreased in left frontal and right prefrontal regions in non-responder (Ozekes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cordance, which is related to absolute and relative spectral powers derived from the resting EEG, increased after HFL-rTMS in both delta and theta bands at left frontal and all right electrodes, except for the F8 electrode, in responders, whereas it decreased in left frontal and right prefrontal regions in non-responder (Ozekes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…2005 a ) as well as prefrontal cordance increase in the theta band (Ozekes et al . 2014) following successful rTMS may reflect the improvement of the cortical GABA B receptor-mediated inhibitory functioning, and increased metabolic activity and blood flow perfusion in frontal regions, seen with rTMS of the DLPFC. More comprehensive studies that include multimodal biological markers are needed to better understand the antidepressant mechanism of DLPFC-rTMS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…36 In addition, a series of studies of subjects with MDD undergoing antidepressant treatment have examined changes in synchrony using qEEG power or cordance (a measure derived from power normalized across frequency bands and electrode sites). These studies have consistently shown that changes in theta and alpha power 35,39,40 or cordance with a range of antidepressant medications, [41][42][43][44][45][46][47] rTMS, [48][49][50] or DBS 51 are strongly predictive of clinical response or remission with active treatment. Regional changes in brain oscillatory synchrony appear to be relatively specific for response to medication and not placebo, 31,52 and to distinguish between the effects of medication and placebo on brain function in healthy control subjects.…”
Section: The Development Of Ips Based On Oscillatory Synchronymentioning
confidence: 95%
“…Furthermore, LORETA validation has been based on accepting as ground truth, the localization findings obtained from invasively implanted depth electrodes, as evident by several studies on epilepsy (66-68) and cognitive ERPs (69). Current density values were computed in eight frequency bands delta (0.5-3.5 Hz), theta (4-8 Hz), alpha-1 (8.5-10 Hz), alpha-2 (10.5-12 Hz), beta-1 (12.5-18 Hz), beta-2 (18.5-21 Hz), beta-3 (21.5-30 Hz), and gamma (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). These frequency bands were defined on the basis of factorial analysis of EEG records and are part of the guidelines and recommendations for the analysis of EEG records in the field of medical electrophysiological research (70).…”
Section: Eloreta Calculationmentioning
confidence: 99%
“…Several recent QEEG studies have partially demonstrated the ability to predict rTMS treatment response (14,31). Among the findings, a non-response or poorer response to treatment is characterized as: a change of power in theta (31)(32)(33), alpha (34), and beta (30) bands in the frontal cortex, prefrontal beta or theta cordance; decrease/unchanged between the baseline and first week of rTMS application (31,35,36); slowing of the anterior alpha peak or a decrease in its frequency (31); larger amplitude of evoked potential P300 (31); no increase in the Lempel-Ziv complex (from minute 1 to 2) in the alpha band (37); and a change in the beta phase-locking values (38).…”
Section: Introductionmentioning
confidence: 99%